2022
DOI: 10.3390/nu14091693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Red Ginseng Concentrate Intake on Stool Characteristic, Biochemical Parameters, and Gut Microbiota in Elderly Korean Women

Abstract: Fermented red ginseng (FRG) has been used as a general stimulant and herbal medicine for health promotion in Asia for thousands of years. Few studies have investigated the effects of FRG containing prebiotics on the gut microbiota. Here, 29 Korean women aged ≥ 50 years were administered FRG for three weeks to determine its effect on stool characteristics, biochemical parameters, and gut microbiome. Gut microbial DNA was subjected to 16S rRNA V3–V4 region sequencing to assess microbial distribution in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Additionally, research on elderly Korean women showed that the consumption of fermented red ginseng (RG) modified 20 distinct bacterial species, thereby enhancing overall wellbeing via its impact on defecation, biochemical parameters, and metabolism ( Lee et al, 2022 ). Eun et al (2023) found that the addition of WERG and its subsequent microbial conversion via the fermentation of RG resulted in alterations in the composition of the GM, exhibiting characteristics of both RG and fermented RG, which were linked to an improved obesity phenotype and glucose balance.…”
Section: Therapeutic Intervention For Amd With Tcmmentioning
confidence: 99%
“…Additionally, research on elderly Korean women showed that the consumption of fermented red ginseng (RG) modified 20 distinct bacterial species, thereby enhancing overall wellbeing via its impact on defecation, biochemical parameters, and metabolism ( Lee et al, 2022 ). Eun et al (2023) found that the addition of WERG and its subsequent microbial conversion via the fermentation of RG resulted in alterations in the composition of the GM, exhibiting characteristics of both RG and fermented RG, which were linked to an improved obesity phenotype and glucose balance.…”
Section: Therapeutic Intervention For Amd With Tcmmentioning
confidence: 99%
“…Fermented red ginseng (fRG) undergoes processing that alters its chemical composition, potentially augmenting the concentration of active compounds and yielding novel bioactive metabolites ( 96 ) ( 97 ). In contrast to conventional red ginseng (RG), fRG exhibits enhanced pharmacological properties, offering promising prospects for augmenting immune function, enhancing energy levels, ameliorating cognitive function, and fostering overall health and well-being.…”
Section: Preclinical Evidence Of Fmt In Treating Depressionmentioning
confidence: 99%